The Involvement of the Papuan People’s Assembly in the Democratic Process: A Study of the 2024 Southwest Papua Gubernatorial Election - Irsat; Muhamad, Sofyan (Gema Kampus IISIP YAPIS Biak, 2026)
Abstract The 2024 West Papua Governor Election is a significant moment in the practice of democracy in the special autonomous region, while also testing the institutional role of the Papuan People's Assembly as a cultural representation of the Indigenous Papuans (OAP). This research aims to analyse the role of the West Papua Regional People's Assembly in supporting the organisation of gubernatorial elections and to assess its compliance with the mandate of the Papua Special Autonomy Law. The research uses a qualitative approach with a case study design. Data was collected through in-depth interviews, observations, and documentation at relevant institutions, namely the West Papua MRP, the West Papua General Election Commission, and representatives of indigenous institutions and community leaders in the West Papua region. Data analysis was conducted through the stages of data reduction, data presentation, and conclusion drawing, using triangulation techniques to ensure data validity. The research findings indicate that the West Papua Regional People's Assembly has played a substantive role in protecting the political rights of OAP by channelling the aspirations of indigenous communities, verifying the status of OAP candidates for regional head, and providing input and recommendations in the governor nomination process. However, this research also found limitations in the implementation of the MRP's authority because the recommendations issued do not have legally binding consequences for election organisers. This condition creates tension between cultural legitimacy based on Special Autonomy and procedural legitimacy based on election regulations, which impacts socio-political conflict during the 2024 gubernatorial election stage. This research concludes that strengthening regulatory harmonisation and inter-agency coordination is key to ensuring the protection of OAP political rights runs in tandem with legal certainty in the conduct of elections in special autonomous regions.